FORMULATION AND IN-VITRO EVALUATION OF METFORMIN HYDROCHLORIDE LOADED MICROSPHERES FOR ORAL CONTROLLED RELEASE - Akasha, Abdulrhman Ahmed (Innoriginal: International Journal of Sciences, 2018)
Biodegradable microspheres may develop improved drug delivery system to gastrointestinal tract, for treatment of Diabetes. Metformin hydrochloride have the ability to produce thus effect for extended period.The Objective of this Work to prepare metformin hydrochloride microspheres by using ethyl cellulose and polyvinyl alcohol as the retardant material with entrapment efficiency and extended release using solvent evaporation techniques.Also, the microspheres were prepared by the double emulsification technique with a yield (40%) are characterized . The Characterization was included : Optical microscopy, Scanning electron microscopy (SEM), Study the compatibility between the selected polymer and metformin hydrochloride by using IR and study the interaction between drug and polymer as well as the microspheres-drug polymer thermal behaviour and crystallinity by using DSC and XRD respectively.Drug release studies were conducted using the dissolution apparatus, the dissolution medium was phosphate buffer at pH 6.8. However the release of loaded metformin hydrochloride in microspheres occurred gradually of 30% up to 8 hours compared to the control which completely released within two hours. Key wards: Metformin, Ethyl cellulose, Polyvinyl alcohol, SEM, Evaporation techniques, DSC, XRD.